Serum polyunsaturated fatty acids and hearing threshold shifts in adults in the United States: A cross-sectional study - Long, Lili; Jia, Zhenchao; Tang, Xinghua (Frontiers in Public Health, 2022)
Background: Few studies have evaluated the association of polyunsaturated fatty acids (PUFAs) with hearing level. This study aimed to investigate the association between serum PUFAs and hearing threshold shifts of US adults. Methods: 913 adults from the National Health and Nutrition Examination Survey (NHANES) 2011-2012 were investigated. Multivariate linear regression analyses were conducted to evaluate the associations. Results: In general, some of 11 serum PUFAs were inversely associated with low-frequency thresholds, especially in men, and were positively related to high-frequency threshold, particularly in the 40-59 years old cohort; some of the serum PUFAs were positively associated with both hearing threshold subgroups in women. Conclusions: Some PUFAs tend to be beneficial for low-frequency hearing status, and detrimental to high-frequency hearing threshold. The status of being male might play a protective role, and that of being female or middle-age might be detrimental in the effect of PUFAs on hearing function.